Novel Method for Quantification of Residual Solvent by Head-Space Gas Chromatography for Phenylephrine Hydrochloride USP (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
The manufacturing process of phenylephrine hydrochloride drug substance contains the use of different solvents in synthesis. USP monograph doesn’t provide method for the residual solvents of Active Pharmaceutical Ingredients (API) as the usage of solvents in manufacturing process depends on route of synthesis. Thus, a novel method has been developed and validated as per ICH guidelines for the quantification of solvents in APIs. The method has been developed for the quantification of ethanol, methanol and isopropanol residual solvents present in phenylephrine hydrochloride USP by Head-Space Gas Chromatography (HS-GC) using Agilent GC-7890B with HS-7697A and Restek MXT-502.2 (diphenyl / dimethyl polysiloxane) 105m x 0.53mm x 3.0µm column. The method has been validated according to ICH Q2R2 guidelines with validation parameters including Specificity, Linearity, Limit of Detection (LOD)/ Limit of Quantification (LOQ), Precision (System precision, Method precision, LOQ Precision), Accuracy. The system precision obtained the %RSD of 2.5, 2.7 and 2.7 and the LOQ was established as 23.5 ppm. 39.0 ppm and 16.4 ppm respectively for ethanol, methanol and isopropanol. The LOD of 7.7 ppm, 12.8 ppm and 5.4 ppm for ethanol, methanol and isopropanol indicated the sensitivity of the method for the detection of analytes. The linearity range of 1% to 100% level of specification revealed the correlation coefficient of 0.9987, 0.9978, 0.9991 respectively for ethanol, methanol and isopropanol solvents.